ANALISIS FAKTOR GEOGRAFI DALAM PEMBUDIDAYAAN TANAMAN PORANG DI DESA WATUMBELAR KECAMATAN LEWA TIDAHU KABUPATEN SUMBA TIMUR - Wandal, Marselinda L; Wulakada, Hamza Huri; Hasan, Muhammad Husain (Jurnal Geografi, 2022)
This study aims to (1) find out how geographical factors affect the cultivation of porang plants in Watumbelar Village, Lewa Tidahu District, East Sumba Regency. The research conducted in Watumbelar Village, Lewa Tidahu District, East Sumba Regency. This type of research used a qualitative approach. .Informal research in this study is all porang cultivation in this research informants as many as 6 groups consisting of 2 people each group and 4 people from village aporators so the number of informants is 16 respondents with purposive sampling methodsampling. The research used a classifier structure in basic translation units.data collection techniques used techniques, interviews, and documentation. Data analysis techniques are data collection, data reduction, data presentation and drawing conclusions. The results of the study show that 1. .Geographical factors in porang cultivation in Watumbelar village is very good because climate factors are very supportive of farmers, with temperature of 23-35 C˚ while rainfall is between 300-500 mm. The soil has a loose texture and rich in nutrients, making it suitable for cultivation porang plants. The availability of water are dug wells, and solar water can be utilized as well as the environmental conditions of farmers to conserve trees as protection from direct sunlight, 2. .cultivation of porang plants in Watumbelar Village, the first thing to do is preparing the land by clear then couse and make embankments. Second seed preparation. The third planting process, fourth maintenance, ad fifth harvest.